Pengaruh Adversity Quotient Terhadap Kesuksesan Berwirausaha (Studi Empiris Pada Wirausahaan Di Kelurahan Tanjung Rejo Kecamatan Medan Sunggal) - Formaida Tambunan (Universitas Negeri Medan, 2020)
The purpose of this study is to examine and analyze the effect of adversity quotient on entrepreneurial success. The population in this study were all entrepreneurs in the Tanjung Rejo Village, Medan Sunggal District and the sample was the total population of 101 respondents. This type of research in this research is quantitative associative research. The data in this study consisted of primary data obtained through a questionnaire while secondary data were obtained from Tanjung Rejo Sub-District, Medan Sunggal District, which was then processed and analyzed by regression analysis. The results showed that adversity quotient influences entrepreneurial success. Adversity quotient in an entrepreneur is a person's ability to face various difficulties and process those difficulties with their intelligence so that they can be resolved. Adversity quotient can help entrepreneurs to strengthen their ability and perseverance in dealing with various problems or difficulties when carrying out their activities as an entrepreneur. Based on the data obtained it can be concluded that adversity quotient influences entrepreneurial success.